Pengaruh Pembinaan Kewirausahaan terhadap Penguatan Ekonomi Daerah: Studi Berbasis Konsep Bisnis UMKM dan Kinerja Keuangan Daerah di Sulawesi Selatan (2019–2024) - Wahyuni; Mochammad Fadhil Abdullah (PT Bukuloka Literasi Bangsa, 2026)
This study aims to analyze the effect of entrepreneurship coaching on strengthening the regional economy by using MSME performance as a mediating variable. Regional economic conditions are greatly influenced by the productivity of MSMEs, which are a dominant sector in Indonesia's economic structure. Entrepreneurship coaching is seen as a form of strategic intervention that can increase the capacity of business actors through the improvement of knowledge, skills, and managerial abilities based on modern business concepts. This study uses a quantitative approach with secondary data on MSME performance and regional economic indicators in South Sulawesi Province for the period 2019–2024, and supports empirical findings through references to the latest scientific publications. The results show that entrepreneurship coaching has a significant positive effect on MSME performance, as well as on strengthening the regional economy both directly and through the mediation of MSME performance. This study reinforces the findings of Mustamin & Wahyuni (2024) that competency-based entrepreneurship assistance can improve the sustainability of community businesses, and is relevant to the findings of Muchtar Lutfi, Wahyuni & Hamris (2025) regarding the importance of effective financial management in strengthening the regional economy. Keywords: Entrepreneurship coaching, SMEs, SME performance, regional economy, business concept